RURAL TOURISM IN THE BORDER AREA ROMANIA- SERBIA - Tudorica, Andra-Valentina (Economics of Agriculture, 2011)
Rural tourism is an important factor with signifcant implications in the economic sphere of any region that provides favorable development of this sector in its various forms. Border area between Romania and Serbia covers the south-east of the Carpathian Basin and includes the counties of Timis, Caras-Severin and Mehedinti from Romania and Borski districts, Branicevski, South Banat, North Banat and Central Banat from Serbia, an area over 39,000 km2 with a population of about 2.3 million. Rural tourism can develop only to the extent that their tourism activity as a whole forms a strong market. The most important elements underlying the design of economic activities are armed with permanent market analysis and implementation of various tourism products marketing.